Integration of artificial neural networks for multi-source energy management in a smart grid - Eziitouni Jarmouni; Ahmed Mouhsen; Mohammed Lamhammedi; Hicham Ouldzira (Institute of Advanced Engineering and Science, 2021)
Among the most widespread renewable energy sources is solar energy; Solar panels offer a green, clean, and environmentally friendly source of energy. In the presence of several advantages of the use of photovoltaic systems, the random operation of the photovoltaic generator presents a great challenge, in the presence of a critical load. Among the most used solutions to overcome this problem is the combination of solar panels with generators or with the public grid or both. In this paper, an energy management strategy is proposed with a safety aspect by using artificial neural networks (ANNs), in order to ensure a continuous supply of electricity to consumers with a maximum solicitation of renewable energy.